Special Issue on Trends in Inequality: Social, Economic and Political - Ardeni, Pier Giorgo (Journal of Income Distribution®, 2019)
In this issue of the Journal of Income Distribution, a very specific selection of those papers is presented. The papers are a significant sample of the contributions presented at the conference held on November 2-4, 2017 in Bologna, Italy, organized by the Cattaneo Institute Research Foundation, entitled Trends in inequality: social, economic and political issues.